Fast ForWord Program on phonological processing and auditory discrimination of children with learning disabilities - Torres, Evangeline C. (2010)
This study is a single case research using Multiple Baselines-Across Peoples Design on the effects of Fast ForWord (FFW) on the phonological processing and auditory discrimination of children with learning disabilities and/or attention deficit hyperactivity disorder. Fast Forword is a reading intervention program developed by the Scientific Learning based on the principles of neuroscience and brain plasticity. The focus of the study was investigate the reading skills development of three children after 40 sessions of this program in a span of two months. The participants were ages 6, 10, and 13 also in the senior kinder, grade 4, and grade 6 levels, respectively. Included in this are the other researches on Fast ForWord , brain plasticity, the two exceptionalities tackled, as well as their effects on reading. Measurement of efficacy was through pre- and post-test, using the standard assessment tools, specifically the Comprehensive Test of Phonological Processing and the Goldman- Fristoe-Woodcock Test of Auditory Discrimination. The weekly reports generated from the program were All the also to establish frend in completion of the activities in the Fast ForWord modules. Specific FFW modules used were the FFW Language v.2, FFW Language Basics, and FFW Reading Prep, FFW Language to Reading, FFW Reading 1, FFW Literacy, and FFW Literacy Advanced. All the participants experienced improvement in phonological memory, phonological awareness, rapid naming, and auditory discrimination in both the Quiet and Noise Subtests in various degrees.